ECB Foreign Exchange Intervention and the Euro: Institutional Framework, News and Intervention - Rasmus Fatum; Michael M. Hutchison (University of Copenhagen, Economic Policy Research Unit (EPRU), 2002)
Using a unique intervention news data set, this paper investigates the impact of ECB intervention and intervention-related news (newswire reports) on the euro exchange rate. A time-series study of news generated by ECB officials and market participants regarding intervention and the value of the euro as well as an event study of firm reports of ECB intervention is conducted. Both studies find significant short-run effects on the euro value, while only negative statements (official statements denying past intervention or ruling out future intervention) appear to have persistent effects.
Keywords: 330; Wechselkurspolitik; Euro; Zentralbank; Signalling; Ankündigungseffekt; EU-Staaten